Analisis Praktik Pembelajaran Lierasi dan Numerasi di UPT SPF SD Negeri Mattoangin 1 Kota Makassar - Mustamin, Andi Nurzainah Ramadhani (Lembaga Yasin AlSys, 2024)
Numeracy literacy ability is a person's ability to solve a problem in the context of everyday life, by involving mathematical knowledge and skills to carry out reasoning in the form of analysis of the information displayed so that the right decision can be made in solving it. This research aims to find out how the numeracy literacy skills of students at SD Negeri Mattoangin 1 Class V in Makassar City are. The research method is a quantitative descriptive analysis method. Indicators of numeracy literacy abilities are (1) the ability to use various kinds of numbers and symbols to solve practical problems in various contexts of daily life, (2) the ability to analyze information displayed in various forms (graphs, tables, charts, etc.), ( 3) and the ability to interpret the results of analyzes that have been carried out to predict and draw conclusions. The instrument used to collect data was a description test with 6 questions on number pattern material. The results of the research show that the level of numeracy literacy skills of students at SD Negeri Mattoangin 1 based on an overall average score of 14.85 is still relatively low. The average value of the numeracy literacy skills of students in the high group was 34.17, the medium group was 11.96, and the low group was 3.57.